1999
DOI: 10.1177/026010609901300201
|View full text |Cite
|
Sign up to set email alerts
|

Food Coping Strategies: A Century on from Rowntree

Abstract: The objectives of this study were to update Rowntree's food estimates to bring them into line with contemporary food habits and changing lifestyles; to determine whether food budgeting/ coping strategies of low income households observed by Rowntree at the turn of the century were still prevalent in low income groups today: and to evaluate whether expenditure by low income households on food was sufficient to meet minimum dietary recommendations. Two hundred questionnaires were completed face to face with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Previous research demonstrates higher costs associated with eating a healthful diet [47,48] with the average cost for a healthy food basket for a typical family representing over a third (31%) of families’ household income [14]. Women from low income families often make sacrifices to their diet by reducing food quality and quantity of healthy foods purchased, and providing healthier foods/meals for their partner or children before their own [49]. These strategies are adopted in order to stretch out the budget and manage other basic needs including shelter, fuel, clothing and other essential commodities [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research demonstrates higher costs associated with eating a healthful diet [47,48] with the average cost for a healthy food basket for a typical family representing over a third (31%) of families’ household income [14]. Women from low income families often make sacrifices to their diet by reducing food quality and quantity of healthy foods purchased, and providing healthier foods/meals for their partner or children before their own [49]. These strategies are adopted in order to stretch out the budget and manage other basic needs including shelter, fuel, clothing and other essential commodities [49].…”
Section: Discussionmentioning
confidence: 99%
“…Women from low income families often make sacrifices to their diet by reducing food quality and quantity of healthy foods purchased, and providing healthier foods/meals for their partner or children before their own [49]. These strategies are adopted in order to stretch out the budget and manage other basic needs including shelter, fuel, clothing and other essential commodities [49]. A recent systematic review, which aimed to determine the impact of food subsidy programs on the nutritional intake and health status of disadvantaged adults in high income countries, reported an increase in fruit and vegetable intake by 1–2 serves per day in disadvantaged women through targeted fruit and vegetable subsidies with nutrition education [50].…”
Section: Discussionmentioning
confidence: 99%
“…Even with efficient purchasing strategies 52-55 , the food budget may not suffice for a diet that is both socially acceptable and nutritious. Indeed, both in France 29 and in the US 56 , the lowest cost required to achieve a nutritionally adequate diet is higher that the actual spending on food at home by low income households.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies have reported that higher-quality diets are associated with higher diet costs (1,2) and are more likely to be consumed by higherincome groups. Whether food costs pose a barrier to dietary change, especially for low-income consumers, remains an open question (3,4). Whereas some reports suggest that all Americans, even those receiving food assistance, can afford a healthy diet (5,6), other reports suggest that healthy diets are unaffordable for lower-income consumers (7).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas many studies on food purchases have been done at the household level, establishing links to nutrition and health requires that daily diet costs be estimated for the individual. The specific objective of the current study was to compare 2 approaches for estimating daily dietary costs among a group of low-income women in California: 1) the timeintensive food expenditure 24-h recall approach (method 1) and 2) the relatively easy food-frequency questionnaire (FFQ) 4 approach (method 2). Our overall goal was to use the existing time-intensive method to validate a new simplified approach to collecting food expenditure information for a large sample, such as that used for a nationally representative study such as NHANES.…”
Section: Introductionmentioning
confidence: 99%